Preparation and storage of frequency-uncorrelated entangled photons from cavity-enhanced SPDC - Jin, X; Yang, J; Zhang, H; Dai, H; Yang, S; Zhao, T; Rui, J; He, Y; Jiang, X; Yang, F; Pan, G; Yuan, Z; et al. (2011)
We report the preparation and storage of frequency-uncorrelated cavity-enhanced SPDC entangled photons. The frequency correlation is eliminated with a suitable pulsed pump. The storage of a single photon entangled with another flying photon is demonstrated. © 2011 OSA.